Supplements to the generalized quantitative assessments of benthic macrofauna in the Far Eastern Seas and adjacent waters of the Pacific Ocean. Report 1. Regional features of distribution for biomass of fish - Vyacheslav P. Shuntov; Igor V. Volvenko (Известия ТИНРО)
Long-term information on mean annual biomass of the main taxa of bottom and demersal fishes on the shelf and upper continental slope (down to 2025 m) in the Far Eastern Seas and adjacent Pacific waters is summarized. Mean annual biomass of fish in the benthic layer (without pelagic species) is estimated as 9.8. 106 t (60.2 % in the Okhotsk Sea, 20.4 % in the Bering Sea, 11.2 % in the Pacific waters at Kuril Islands, 4.1 % in the Japan Sea, and 4.1 % in the Pacific waters at Kamchatka). Schemes of these species distribution in the pelagic layers are presented, too. Even truly bottom fishes rise to the pelagic layers sometimes (mostly in the nighttime). Eggs, larvae and juveniles of many demersal and benthic species dwell mainly in the pelagic layers, transported by currents everywhere including the open waters beyond the continental shelf and slope; elder fish, from the stage of fingerlings, are able for migrations, even against stream. Biomass of the species majority is proportional to square of shelf and slope, with exception of the species associated with complicated bottom topography (rocks, canyons, guyots, etc.), in particular at steep slopes.